Prenatal and perinatal risk factors of food allergy in Taiwanese young children - Lin Ching-Wei, MD; Tsai Yi-Fen, MSc; Su Yu-Tsun, MD; Yu Hong-Ren, MD, PhD; Li Hsing-Jung, MD; Hung Chih-Hsing, MD, PhD; Liu Li-Fan, PhD; Tsai Hui-Ju, PhD; Wang Jiu-Yao, MD, DPhil (World Allergy Organization Journal, 2022)
Background: In recent decades, the prevalence of food allergy (FA) in children has increased in Western countries; however, there have been only limited studies on FA, especially among young children, in Asian countries, including Taiwan. In this study, we identified prenatal and perinatal risk factors associated with FA in young children in Taiwan. Methods: For this prospective birth cohort study, we adopted the Southern Taiwan Allergy Research Alliance (STARA)-FA questionnaire to collect data related to prenatal and perinatal risk factors and self-reported allergic symptoms in children aged 1–3 years in the well-baby clinics of 4 medical centers located in 3 cities, Chia-Yi, Tainan, and Kaohsiung, Taiwan. The STARA-FA questionnaire consisted of 99 questions to investigate the association of prenatal and perinatal risk factors with FA. Results: We recruited 903 young children aged 1–3 years in Taiwan. Among those, 95 (14.7%) children had allergic reactions to foods. The most common food allergens were eggs (26/95, 27.3%), milk (22/95, 23.2%), fruits (13/95, 13.7%), and seafood (12/95, 12.6%). We also found that there were 134 (14.8%) children with eczema, 86 (9.5%) with wheezing, and 240 (26.6%) with rhinitis. Children with a personal history of eczema (adjusted odds ratio [AOR], 2.48; 95% confidence interval [CI], 1.38–4.45) and a family allergy history (AOR, 2.06; 95% CI, 1.18–3.57) had a significantly increased risk of FA. Maternal peanut consumption during pregnancy was associated with a decreased risk of FA in children (AOR, 0.57; 95% CI, 0.33–0.98). Conclusions: In this study, the prevalence of FA in a cohort of Taiwanese young children was 14.7%. Risk factors associated with FA were a personal eczema history and a family allergy history, which might serve as predictive or prevention factors for the development of FA in young children in Taiwan.